Analisis Tantangan dan Peluang Perkembangan Globalisasi Ekonomi dalam Hukum Bisnis Di Indonesia - hasibuan, nelson; Hasiholan Sihaloho; Subhan Zein; Mario Alberto Manodohon (VYAVAHARA DUTA, 2024)
Globalization as a fast-growing interdependence and connection in the world of trade and finance. Globalization is not only limited to the phenomenon of trade and financial flows that are growing increasingly widespread, this is due to other trends driven by communication. What are the challenges and opportunities for the development of economic globalization in business law in Indonesia? 1) Competition regulation, business law regulates fair competition and prohibits business practices that harm consumers or competitors. This ensures that the market remains healthy and prevents monopolies that harm the economy. Contracts and contract law. 2) Business law governs the creation, interpretation, and enforcement of contracts. This provides legal certainty for parties involved in business transactions and allows contractors to rely on contract fulfillment. 3) Banking and financial arrangements, regulation and supervision of all such financial activities shall be carried out with integrity. 4) Protection of Intellectual Property Rights (IPR). Business law protects copyrights, patents, trademarks, and industrial designs that encourage innovation and the creation of new goods and services. It provides incentives to companies and individuals to invest in research and development.